ACCELERATION ANALYSIS USING THE CRASHING METHOD IN THE SDN KUTISARI 2 DEVELOPMENT PROJECT - Firdaus, Muhammad Bayu; Tjendani, Hanie Teki; Witjaksana, Budi (Transpublika Publisher, 2023)
In the construction of the Kutisari 2 SDN Project, there were several obstacles that hampered the implementation of the project, such as heavy rainy weather. The aim of the research is to determine the cost and acceleration time for the construction of the SDN Kutisari 2 Project. The research design was carried out to identify the time and costs of implementing the building construction completion project. The research was conducted at CV.Nisya Multi Bintang as the implementing contractor with a budget of Rp. 1,614,171,924 for 165 calendar days. The research subjects were contractors completing work on the Kutisari 2 Elementary School Development Project. This research used secondary data from the Draft Expenditure Budget, Schedule, weekly reports and project cost costs. Data analysis used Microsoft Project 2016 software. The results of the research stated (1) The duration of the Crashing was 8 calendar days with work that was on the Critical Work Route for the Construction of School Facilities, Infrastructure and Utilities at SDN Kutisari 2, namely water proofing coating with fiber on the 2nd floor, cleaning location to the end, B-0 work to cover 2nd floor columns, 2nd floor column cutting work, and floor screading work. (2) From the initial cost of the Kutisari 2 SDN School Facilities, Infrastructure and Utilities Construction Work Project, namely Rp. 1,164,171,924 with additional costs due to Crashing of Rp. 24,569,780 so the total costs due to the Crashing are Rp. 1,638,741,704.